2019
DOI: 10.1016/j.euromechflu.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Measuring surface gravity waves using a Kinect sensor

Abstract: We present a technique for measuring the two-dimensional surface water wave elevation both in space and time based on the low-cost Microsoft Kinect sensor.We discuss the capabilities of the system and a method for its calibration. We illustrate the application of the Kinect to an experiment in a small wave tank.A detailed comparison with standard capacitive wave gauges is also performed.Spectral analysis of a random-forced wave field is used to obtain the dispersion relation of water waves, demonstrating the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition to coded light 48 , other depth sensing technologies have been used to map the water surface including scanning lidar 49 , stereo imaging 50 , polarimetric imaging 51 , and ultrasonic sensing 52 . A future implementation of our system toward deployment in open waters may utilize one, or a combination of, these techniques to map the surface of water.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coded light 48 , other depth sensing technologies have been used to map the water surface including scanning lidar 49 , stereo imaging 50 , polarimetric imaging 51 , and ultrasonic sensing 52 . A future implementation of our system toward deployment in open waters may utilize one, or a combination of, these techniques to map the surface of water.…”
Section: Discussionmentioning
confidence: 99%
“…The KV1 sensor shows more scattered perceived depths, which suggests that it may not be very reliable soon after the solution is allowed to rest. Previous studies have used KV1 [ 40 , 42 , 43 ], however, these results would suggest that KV2 is more reliable when there is a chance of TiO 2 settlement. These data demonstrate two key findings: (1) KV2 again shows a more stable response than KV1; (2) there is a decrease in measured depth over time, meaning that fluid should be continuously mixed (perhaps by turbulence in the case of a turbulent flow) in order to maintain accuracy.…”
Section: Sensor Accuracy and Minimum Colourant Concentrationmentioning
confidence: 99%
“…While KV1 approached the correct value more quickly, neither sensor showed a reliable measurement until after a concentration of 0.01% by mass. Previous studies did not examine the accuracy of measurement as a function of TiO 2 concentration [ 40 , 42 , 43 ], and did not state the TiO 2 concentration used, so it is impossible to know whether those measurements were collected with an appropriate amount of TiO 2 . Martinez-Aranda et al [ 41 ] stated a TiO 2 concentration of 1.2%, which Figure 8 shows to be approximately 100 times greater than that which is necessary.…”
Section: Sensor Accuracy and Minimum Colourant Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reflectivity of the air/water interface is low (approx. 2% reflected [15]), and previous attempts using depth sensors with active illumination have shown that they typically require the addition of dye to the water [16]. Furthermore, techniques based on indirect ToF have difficulties dealing with multi-path returns [17], which is a problem for laboratory-based experiments where an additional return signal is expected from the basin floor.…”
Section: Background and Introductionmentioning
confidence: 99%